Impacto de la Implementación de la Normas Internacional de Información Financiera (NIIF), en la compañía “Hoteles y Servicios Almendral Cía. Ltda.” de la ciudad de Loja. Año 2012. - Arévalo Alvarado, Maricela del Carmen (2014)
Implementation IFRS (International Financial Reporting Standard), in the company "Hoteles y Servicios Almendral Cía. Ltda." provides in the presentation of financial information in this institution. At the same time, markets are integrated in the main capitals of the world, and the logic of a single set of accounting standards is evident. To understand the impact that generated the IFRS, some institutions worked hard to involve to the company in this new financial language, through staff training, with the opportunity to improve the financial system the company, because this financial language turns out to be transparent, comparable and useful for decision-making of its shareholders and directors. To know the accounting impact generated by the implementation of IFRS in the company, it was comparing the results obtained in the current financial statements with the above and by the reclassification of accounts, and enforcement, likewise the loss is removed existing accounting, increasing transparency and confidence for investors. The results of this investigation also contribute for managers to consider integrating a unique module for the fixed assets of the company in its accounting system.